2005
DOI: 10.1164/rccm.200501-142oc
|View full text |Cite
|
Sign up to set email alerts
|

Role for CXCR6 and Its Ligand CXCL16 in the Pathogenesis of T-Cell Alveolitis in Sarcoidosis

Abstract: T cells coexpressing CXCR3 and CXCR6 act coordinately with respective ligands and Th1 inflammatory cytokines in the alveolitic/granuloma phases of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
79
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 28 publications
4
79
2
Order By: Relevance
“…The T-bet control of CXCR3 expression is of particular interest in sarcoidosis because this chemokine receptor plays a pivotal role in recruiting T-cells to the lungs with subsequent granuloma formation [4]. In this study, we observed a strong correlation between T-bet and CXCR3 and IFN-c expression in BAL cells obtained from sarcoid lungs.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The T-bet control of CXCR3 expression is of particular interest in sarcoidosis because this chemokine receptor plays a pivotal role in recruiting T-cells to the lungs with subsequent granuloma formation [4]. In this study, we observed a strong correlation between T-bet and CXCR3 and IFN-c expression in BAL cells obtained from sarcoid lungs.…”
Section: Discussionsupporting
confidence: 53%
“…To address the role for T-bet in sarcoidosis from this aspect, we studied its relationship with selected cytokines/receptors implicated in disease pathogenesis. Of the studied chemokine receptors, we observed a strong correlation between T-bet and CXCR6, a receptor co-expressed on CXCR3 T-cells in sarcoidosis [4]. Furthermore, a strong correlation was observed between T-bet and CCL5 and CXCL10, two chemokines that play an important role in the recruitment of T-cells to the sarcoid lungs [4,[15][16][17]19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations